Structure fixing material for interior of hydrogen energy power pack and preparation method of structure fixing material
By using a fixed material with high thermal conductivity formed by combining raw materials such as polyether polyols in the power pack of hydrogen-energy electric bicycles, the problem of poor thermal conductivity in the power pack is solved, the mechanical performance and service life are improved, and the power system is ensured to be reliable. Sex and safety.
Patent Information
- Application Number
- CN202411597681.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-07
AI Technical Summary
The thermal conductivity of the internal fixing materials of the hydrogen-energy electric bicycle power pack is poor, resulting in reduced power and short service life of the components in the power pack, and it is easy to loosen or fall off during vibration and temperature changes, posing safety hazards.
The raw materials such as polyether polyol, isocyanate, chain extender, thermally conductive additive, sodium polyacrylate, sodium hydroxide, nano-alumina powder, zeolite powder and polyvinyl alcohol are used to form thermal conductivity and high mechanical properties through foaming reaction. The fixing material enhances the stability and durability of the material.
It significantly improves the thermal conductivity and mechanical properties inside the power pack, extends the life of batteries and electronic components, ensures excellent performance in various environments, and provides reliable power system guarantee for hydrogen-energy electric bicycles.
Smart Images

Figure CN119264370A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen-powered electric bicycles, and specifically relates to a structural fixing material used inside a hydrogen-powered power pack. Background Art
[0002] With the increasing global awareness of environmental protection and the adjustment of energy structure, the development of new energy vehicles has become a trend. As a clean and efficient form of energy, hydrogen energy has gradually attracted attention for its application in small vehicles such as electric bicycles. Hydrogen electric bicycles convert chemical energy into electrical energy through hydrogen fuel cells, which then drives the motor to work, achieving zero emissions and low noise, and have significant environmental advantages.
[0003] However, in actual application, the installation and fixation of the components in the hydrogen power pack has become a technical problem that cannot be ignored. Traditional fixing methods often use metal screws or plastic clips, etc. These methods have certain limitations, such as heavy weight, complex installation, poor durability, etc., especially in the face of harsh conditions such as vibration and temperature changes, which can easily cause the power pack to loosen or even fall off. In particular, since the hydrogen power pack will generate heat, the large amount of heat generated will cause the material that fixes the hydrogen power pack components to deform to a certain extent, which will cause the power pack to fall off, posing a safety hazard to users.
[0004] In addition, since the hydrogen power pack contains a hydrogen storage device, the requirements for the fixing materials are more stringent. It not only needs to have good mechanical properties, but also must have excellent thermal conductivity and aging resistance to ensure long-term reliability and safety. Summary of the invention
[0005] In order to overcome the defects of the prior art, the present invention provides a structural fixing material for the interior of a hydrogen energy power pack and a preparation method thereof, which solves the technical problem that the thermal conductivity in the current power pack is poor, thereby reducing the power and service life of various components in the power pack.
[0006] The object of the present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a structural fixing material for the interior of a hydrogen power pack, comprising the following raw materials: Polyether polyol 27.25-34.75 wt%, isocyanate 27.25-34.75 wt%, chain extender 0.25-1 wt%, accelerating agent 0.5-3 wt%, thermal conductive additive 0.5-2 wt%, sodium polyacrylate 0.5-3 wt%, sodium hydroxide 1.5-2.5 wt%, nano alumina powder 5-10 wt%, zeolite powder 5-15 wt%, polyvinyl alcohol 1-4 wt%, polyoxypropylene glycol 1-5 wt%.
[0007] The principle of the present invention is as follows: Polyether polyols: react with isocyanates to form closed polyester prepolymer foams, providing structural support and enhancing cell stability.
[0008] Isocyanate: blowing agent, the double bonds of C and N in N=C=O of isocyanate are broken, connecting the active hydrogen of polyol to form a polymer prepolymer.
[0009] Chain extender: reacts with polyurethane to extend the molecular chain, increase the molecular weight, and improve the mechanical properties of polyester and other products.
[0010] Accelerating agent: speeds up the reaction rate, effectively controls the foaming process, and establishes a good balance between the molecular chain growth reaction and foaming.
[0011] Thermal conductive additive: A composite material with a core-shell structure. On the one hand, it increases the thermal conductivity of the foaming agent through the inner layer material. On the other hand, it coats the outer layer with a thinner protective layer to reduce the electrical conductivity of the foam, which is beneficial to promote the use of the foam in the circuit system.
[0012] Sodium polyacrylate: There are a large number of carboxyl groups (-COOH) and carboxylate groups (-COO-) in the molecular structure of sodium polyacrylate, which can increase the viscosity of the foaming agent, make the foam more delicate and soft, not easy to break, and easier to adhere to and diffuse on the surface of objects, increasing the stability and retention of the foam.
[0013] Sodium hydroxide: a catalyst that accelerates the curing reaction, forms a strong foam structure and promotes the cross-linking reaction in the foam, increasing the stability and strength of the foam. In addition, by adjusting the pH value, sodium hydroxide can ensure that the foam maintains a uniform foam structure and good physical properties during the curing process. In addition, an appropriate amount of sodium hydroxide can improve the storage stability of the foam, prevent it from prematurely curing or deteriorating during storage, and ensure the effectiveness and safety of use. Nano-alumina powder: It has a high hardness and can enhance the hardness of the material, improve the wear resistance, improve the physical properties of the material, and enhance the stability of the material. By adding nano-alumina powder, it can regulate the internal tension of the foam after mixing, prevent the filler from stratifying and sinking, and further increase the consistency of the foam.
[0014] Zeolite powder: absorbs odor and harmful substances in foam, such as ammonia nitrogen, etc., improves the strength of the foam, and enhances its durability and volume stability. In addition, by loading aluminum ions onto zeolite powder, the flame retardancy of the foam is increased.
[0015] Polyvinyl alcohol: Increases the viscosity and adhesion of foam glue, making it easier for foam glue to adhere to objects, while ensuring the stability of foam glue in a humid environment. Polyoxypropylene glycol: Improves the physical properties of foaming glue. Polyoxypropylene glycol makes the foam of foaming glue uniform and delicate, and has higher tensile shear strength.
[0016] In one embodiment, the chain extender is glycerol, diethylene glycol, triethylene glycol, neopentyl glycol, 1,4-butanediol, 1,6-hexanediol, diethylaminoethanol, ethylenediamine, N,N-dihydroxy(diisopropyl)aniline or hydroquinone-bis(β-hydroxyethyl)ether.
[0017] The use of the above-mentioned chain extender can not only improve the physical properties of the fixed material such as strength, toughness, and wear resistance, but also extend the polymer chain and increase the molecular weight of the fixed material, thereby making the thermal conductivity and ductility of the fixed material better. In addition, the use of the chain extender can maintain the performance of the fixed material while reducing the amount of high-cost materials, thereby reducing costs.
[0018] In one embodiment, the chain extender is preferably hydroquinone-bis(β-hydroxyethyl) ether.
[0019] As a chain extender, hydroquinone-bis(β-hydroxyethyl) ether (HQEE) can react with isocyanate groups (-NCO) to extend the polymer chain, thereby significantly increasing the molecular weight of the polymer. High molecular weight polymers generally have better mechanical properties, such as higher strength and toughness; after increasing the molecular weight, the physical properties of the polymer are significantly improved, including tensile strength, tear strength, abrasion resistance and chemical resistance; compared to some other chain extenders, HQEE has lower volatility and toxicity, which makes it safer during use and has less impact on the environment.
[0020] In one embodiment, the accelerating aid is N-methylmorpholine, N,N-dimethylcyclohexylamine, triethylamine, N,N-dimethylbenzylamine, triethanolamine or N,N'-lutidine.
[0021] Accelerating additives can increase the overall reaction rate, reduce the reaction temperature, promote polymer reactions and improve material properties.
[0022] In one embodiment, the thermal conductive additive includes an outer layer and an inner layer, the outer layer is completely coated on the inner layer, the outer layer is aluminum oxide (Al2O3) or copper oxide (CuO), and the inner layer includes at least one of reduced graphene, graphite, perovskite oxide, and perovskite oxide-graphene.
[0023] The outer layer is a non-conductive metal oxide, while the inner layer is mainly a conductive material. The outer metal oxide mainly plays a role in thermal conductivity and reducing the electrical conductivity of the composite. Aluminum oxide and copper oxide have a relatively ordered lattice and can play a better role in thermal conductivity. The internal conductive material has good thermal conductivity and can further play a role in thermal conductivity.
[0024] In one embodiment, the inner layer and the outer layer constitute a sphere and / or a tube bundle structure of a core-shell structure.
[0025] The spherical structure and the tube bundle structure can increase the specific surface area of the outside of the heat-conducting additive, thereby increasing the contact area with the power pack and further improving the heat-conducting effect.
[0026] In one embodiment, the perovskite oxide includes at least one of lanthanum nickelate, lanthanum cobalt nickelate, and lanthanum strontium cobalt iron.
[0027] Lanthanum nickelate, lanthanum cobalt nickelate and lanthanum strontium cobalt iron are all metal oxides with complex structures and multiple properties. Among them, lanthanum nickelate and lanthanum cobalt nickelate have good thermal stability and will not cause thermal decomposition of the overall fixed material due to the high heat emitted by the power pack; while lanthanum nickelate and lanthanum strontium cobalt iron have good thermoelectric properties and can convert part of the heat emitted by the power pack into electrical energy, thereby providing a certain amount of energy for the power pack.
[0028] In one embodiment, the chemical formula of the lanthanum cobalt nickelate is LaNixCoyO3, wherein 0≤x≤0.5, 0≤y≤1; the chemical formula of the lanthanum strontium cobalt iron is La0.6Sr0.4Co(1-y2)Fey2O3, wherein 0≤y2≤1.
[0029] Lanthanum nickelate, lanthanum cobalt nickelate and lanthanum strontium cobalt iron are all metal oxides with complex structures and multiple properties. Among them, lanthanum nickelate and lanthanum cobalt nickelate have good thermal stability and will not cause thermal decomposition of the overall fixed material due to the high heat emitted by the fuel cell. Lanthanum nickelate and lanthanum strontium cobalt iron have good thermoelectric properties and can convert part of the heat emitted by the fuel cell into electrical energy, thereby providing a certain amount of energy for the fuel cell.
[0030] The values of x, y, and y2 can ensure that the obtained thermally conductive solid material has excellent electrical and thermal conductivity. The external aluminum oxide and copper oxide can prevent the internal conductive material from affecting the conductive properties of the coolant due to their insulating properties. The internal conductive material can further assist in thermal conduction due to its conductive properties.
[0031] In one embodiment, the particle size of the perovskite oxide is 20 to 150 nm.
[0032] This particle size can ensure the stability of the overall fixed material structure and is not prone to precipitation.
[0033] In a second aspect, the present invention also provides a method for preparing a structural fixing material for use inside a hydrogen power pack, comprising the following steps: stirring and evenly mixing polyether polyol, isocyanate, chain extender, speed promoter, thermal conductive additive, sodium polyacrylate, sodium hydroxide, nano-alumina powder, zeolite powder, polyvinyl alcohol, and polyoxypropylene glycol to obtain the structural fixing material for use inside a hydrogen power pack.
[0034] It can be prepared by conventional methods, which greatly reduces the difficulty of preparation and the difficulty of operation for operators.
[0035] The beneficial effects of the present invention are: The present invention provides a structural fixing material for a hydrogen-powered electric bicycle power pack. By optimizing the component ratio and adding a heat-conducting additive, the mechanical performance requirements of the internal fixing parts of the power pack are met. At the same time, the thermal management capability of the system is significantly enhanced, the temperature of the power pack during operation is effectively reduced, and the life of the battery and electronic components is extended. In addition, the material has good chemical stability and weather resistance, and can maintain excellent performance in various environments, providing reliable protection for the power system of hydrogen-powered electric bicycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The present invention will be described in more detail below based on embodiments and with reference to the accompanying drawings, wherein: Figure 1 Graph showing the change in temperature of the power pack over time in a test example of the present invention. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the accompanying drawings. Example
[0038] This embodiment provides a structural fixing material for the interior of a hydrogen power pack and a preparation method thereof: The raw materials are as follows: 27.25 g of polyether polyol, 27.25 g of isocyanate, 1 g of 1,6-hexanediol, 3 g of N-methylmorpholine, 2 g of thermal conductive additive (outer layer is alumina, inner layer is graphene), 3 g of sodium polyacrylate, 2.5 g of sodium hydroxide, 10 g of nano alumina powder, 15 g of zeolite powder, 4 g of polyvinyl alcohol, and 5 g of polyoxypropylene glycol.
[0039] The steps are as follows: the above raw materials are stirred and mixed to obtain. The preparation of the thermal conductive additive includes the following steps: acetic acid, acetylacetone and aluminum nitrate are mixed evenly in a mass ratio of 1:7:2, and ammonia water with a mass fraction of 10% is added dropwise to a pH of 6.5 to form an aluminum hydroxide colloidal solution. At room temperature, under stirring mode (300 r / min), graphene is added to the aluminum hydroxide colloidal solution, and the mass ratio of the aluminum hydroxide colloidal solution to graphene is 20:1. Stir for 1 h, filter at room temperature, and collect the solid. 120°C, dry for 3 h, and sinter the dried solid at 1000°C for 2 h under nitrogen protection to obtain the thermal conductive additive. Example
[0040] This embodiment provides a structural fixing material for the interior of a hydrogen power pack and a preparation method thereof: The raw materials are as follows: 34.75 g of polyether polyol, 34.75 g of isocyanate, 0.25 g of diethylaminoethanol, 0.5 g of N,N'-dimethylpyridine, 0.5 g of thermal conductive additive (the outer layer is copper oxide, the inner layer is lanthanum nickelate with a particle size of 20 nm, the chemical formula is LaNiO3), 0.5 g of sodium polyacrylate, 1.5 g of sodium hydroxide, 5 g of nano alumina powder, 5 g of zeolite powder, 1 g of polyvinyl alcohol, and 1 g of polyoxypropylene glycol.
[0041] The steps are as follows: the above raw materials are stirred and mixed to obtain. The preparation of the thermal conductive additive includes the following steps: acetic acid, acetylacetone and copper nitrate are mixed evenly in a mass ratio of 1:7:2, and ammonia water with a mass fraction of 10% is added dropwise to a pH of 6.5 to form a copper hydroxide colloidal solution. At room temperature, under stirring mode (300 r / min), lanthanum nickelate with a particle size of 20 nm is added to the copper hydroxide colloidal solution, and the mass ratio of the copper hydroxide colloidal solution to lanthanum nickelate is 20:1, stirred for 1 h, filtered at room temperature, and the solid is collected. 120°C, dried for 3 h, and the dried solid is sintered at a high temperature of 1000°C for 2 h under nitrogen protection to obtain the thermal conductive additive. Example
[0042] This embodiment provides a structural fixing material for the interior of a hydrogen power pack and a preparation method thereof: The raw materials are as follows: 31 g of polyether polyol, 31 g of isocyanate, 0.625 g of hydroquinone-di(β-hydroxyethyl) ether, 1.75 g of N,N-dimethylbenzylamine, 1.25 g of thermal conductive additive (the outer layer is alumina, and the inner layer is a composite of lanthanum cobalt nickelate (chemical formula LaNi0.5CoO3)-lanthanum strontium cobalt iron (chemical formula La0.6Sr0.4Co0.5Fe0.5O3)-graphene with a particle size of 85 nm), 1.75 g of sodium polyacrylate, 2 g of sodium hydroxide, 7.5 g of nano alumina powder, 10 g of zeolite powder, 2.5 g of polyvinyl alcohol, and 3 g of polyoxypropylene glycol.
[0043] The steps are as follows: the above raw materials are stirred and mixed to obtain. The preparation of the thermal conductive additive includes the following steps: acetic acid, acetylacetone and aluminum nitrate are mixed evenly in a mass ratio of 1:7:2, and ammonia water with a mass fraction of 10% is added dropwise to a pH of 6.5 to form an aluminum hydroxide colloidal solution. At room temperature, under stirring mode (300 r / min), a composite of lanthanum cobalt nickelate-lanthanum strontium cobalt iron-graphene with a particle size of 85 nm is added to the aluminum hydroxide colloidal solution, and the mass ratio of the aluminum hydroxide colloidal solution to the composite of lanthanum cobalt nickelate-lanthanum strontium cobalt iron-graphene is 20:1, stirred for 1 h, filtered at room temperature, and the solid was collected. 120°C, dried for 3 h, and the dried solid was sintered at 1000°C for 2 h in a nitrogen protection manner to obtain the thermal conductive additive.
[0044] Comparative Example Commercial foam glue is used to fix components inside the power pack of the hydrogen electric bicycle.
[0045] Test example Fill the foam glue prepared in Examples 1 to 3 and the comparative example into the spray gun and tighten it to ensure a firm connection with the tank. Aim the nozzle at the gap between the components in the power pack and keep a proper distance from the object. Press the nozzle button on the spray gun tank to start spraying and cover the entire bonding area. Curing for 5 hours.
[0046] At room temperature, turn on the power pack at the same time and read the temperature inside the power pack through the control system.
[0047] The results are as follows Figure 1 As shown, according to Figure 1 The results show that the thermal conductivity of the fixing material prepared by the present invention is significantly higher than that of the fixing material prepared by the comparative example.
[0048] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "bottom", "top", "front", "back", "inside", "outside", "left", "right", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0049] Although the present invention is described herein with reference to specific embodiments, it should be understood that these embodiments are merely examples of the principles and applications of the present invention. It should therefore be understood that many modifications may be made to the exemplary embodiments and that other arrangements may be devised without departing from the spirit and scope of the present invention as defined by the appended claims. It should be understood that the various dependent claims and features described herein may be combined in a manner different from that described in the original claims. It should also be understood that features described in conjunction with individual embodiments may be used in other described embodiments.
Claims
1. A structural fixing material for the interior of a hydrogen power pack, characterized in that: Including the following raw materials: Polyether polyol 27.25-34.75 wt%, isocyanate 27.25-34.75 wt%, chain extender 0.25-1 wt%, accelerating agent 0.5-3 wt%, thermal conductive additive 0.5-2 wt%, sodium polyacrylate 0.5-3 wt%, sodium hydroxide 1.5-2.5 wt%, nano alumina powder 5-10 wt%, zeolite powder 5-15 wt%, polyvinyl alcohol 1-4 wt%, polyoxypropylene glycol 1-5 wt%.
2. The structural fixing material for the interior of a hydrogen power pack according to claim 1, characterized in that: The chain extender is glycerol, diethylene glycol, triethylene glycol, neopentyl glycol, 1,4-butanediol, 1,6-hexanediol, diethylaminoethanol, ethylenediamine, N,N-dihydroxy (diisopropyl) aniline or hydroquinone-di (β-hydroxyethyl) ether.
3. The structural fixing material for the interior of a hydrogen power pack according to claim 2, characterized in that: The chain extender is preferably hydroquinone-bis(β-hydroxyethyl) ether.
4. The structural fixing material for the interior of a hydrogen power pack according to claim 1, characterized in that: The accelerating auxiliary agent is N-methylmorpholine, N,N-dimethylcyclohexylamine, triethylamine, N,N-dimethylbenzylamine, triethanolamine or N,N'-dimethylpyridine.
5. The structural fixing material for the interior of a hydrogen power pack according to claim 1, characterized in that: The thermal conductive additive includes an outer layer and an inner layer, the outer layer is completely coated on the inner layer, the outer layer is Al2O3 or CuO, and the inner layer includes at least one of reduced graphene, graphite, perovskite oxide, and perovskite oxide-graphene composite.
6. The structural fixing material for the interior of a hydrogen power pack according to claim 5, characterized in that: The inner layer and the outer layer constitute a sphere and / or a tube bundle structure of a core-shell structure.
7. The structural fixing material for the interior of a hydrogen power pack according to claim 6, characterized in that: The perovskite oxide includes at least one of lanthanum nickelate, lanthanum cobalt nickelate, and lanthanum strontium cobalt iron.
8. The structural fixing material for the interior of a hydrogen power pack according to claim 7, characterized in that: The chemical formula of the lanthanum cobalt nickelate is LaNixCoyO3, wherein 0≤x≤0.5, 0≤y≤1; the chemical formula of the lanthanum strontium cobalt iron is La0.6Sr0.4Co(1-y2)Fey2O3, wherein 0≤y2≤1.
9. The structural fixing material for the interior of a hydrogen power pack according to claim 5, characterized in that: The particle size of the perovskite oxide is 20 to 150 nm.
10. A method for preparing a structural fixing material for the interior of a hydrogen power pack as claimed in any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing polyether polyol, isocyanate, chain extender, accelerating agent, thermal conductive additive, sodium polyacrylate, sodium hydroxide, nano-alumina powder, zeolite powder, polyvinyl alcohol and polyoxypropylene glycol to obtain the structural fixing material for the hydrogen power pack.